Transfer Of Receivables On Behalf Of The Savings And Loan Cooperative Sahabat Mitra Sejati Rantau Prapat Branch Office - Muhammad Bayu Dwi Arya; Bambang Fitrianto; Siti Nurhayati (International Asia Of Law and Money Laundering (IAML), 2023)
In the business world capital turnover is an indication for it's a good effort. Based on this often entrepreneurs need capital in a short period of time in order to ensure the liquidity of its business, so no longer wait for a fall due on receivables to be collected later the payment. The method generally used to obtain fresh funds in the near future on outstanding receivables is by way of selling its receivables to others who are willing to buy it, generally at a price lower than the value of the bill to be paid by the debtor at maturity. Regarding the high and low prices as well depending on the illiquid receivables and whether there is a guarantee that accompanies the debt. Problems arise when procedure or process of selling the receivables do not meet existing legal provisions, so as to harm the seller this itself in this case the savings and loan cooperative sahabat mitra sejati branch rantau prapat